2016
DOI: 10.1111/polp.12145
|View full text |Cite
|
Sign up to set email alerts
|

Party Promises, Voter Understanding, and Mandate Responsiveness inEastEuropean Politics

Abstract: The literature on reform policy fulfillment after the collapse of Communism identifies mandate responsiveness as the weakest aspect of the quality of democracy in Eastern Europe. We build on this research and specify both direct and interaction effects of party promises and voter understanding on policy outcomes. On the empirical level, we develop a measure of citizen comprehension of party positions to analyze this component of the mandate model, previously omitted in much of the scholarship on the topic. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The probability increases from 0.05 to 0.233, and this relationship is statistically significant ( p = 0.00). The fact that parties appear to fulfill their mandates when it comes to gender equality provides further evidence in support of Kostadinova and Kostadinova (2016) finding that policy domain matters when it comes to mandate fulfillment. It further means that political parties remain a force behind gender equality promotion in the region, contrary to what prior studies have found (Einhorn, 2006; Htun and Weldon, 2018; Kostelecky, 2002; Ristova, 2003; Rueschemeyer, 1998).…”
Section: Analysis and Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The probability increases from 0.05 to 0.233, and this relationship is statistically significant ( p = 0.00). The fact that parties appear to fulfill their mandates when it comes to gender equality provides further evidence in support of Kostadinova and Kostadinova (2016) finding that policy domain matters when it comes to mandate fulfillment. It further means that political parties remain a force behind gender equality promotion in the region, contrary to what prior studies have found (Einhorn, 2006; Htun and Weldon, 2018; Kostelecky, 2002; Ristova, 2003; Rueschemeyer, 1998).…”
Section: Analysis and Discussionmentioning
confidence: 72%
“…Similarly, Roberts (2010), working on postcommunist countries, finds only weak mandate responsiveness when it comes to economic reforms in the region and links it to the constrained policy-making environment that was a function of international integration and loan agreements. At the same time, Lipsmeyer (2009) maintains that postcommunist governments fulfill their campaign promises, but “in a manner different from what has been found in established democracies” (p. 715), and Kostadinova and Kostadinova (2016) report promise fulfillment in the areas of democratization, welfare spending, and education. No study up-to-date, however, has examined mandate fulfillment in the domain of gender equality.…”
Section: Introductionmentioning
confidence: 99%